Pengaruh Pekerjaan Orang Tua Terhadap Status Gizi Anak Kelompok A di TKIT Ananda Jember - Octaverani, Adelia; Nufus, Sholehatun; Badriyah, Fina Qomariyatul; Afriza, Dinda Ayu; Ardini, Dania Auji; Aisiyah, Laily Nur (PG PAUD Universitas Negeri Surabaya, 2023)
Monitoring the nutritional status of children aged 0-6 years can be done at school. Teachers play a role in recognizing the nutritional status of their students. This study aims to identify and monitor the nutritional status of children at TKIT Ananda. This research is a quantitative research with research locations in TKIT Ananda, Jember. The number of samples in this study were 11 samples, namely 6 girls and 5 boys. Data was collected by measuring body weight and height, after which it was analyzed using the z-score method and anthropometric books. Based on the measurement results using the indicators for BB/U, TB/U, BB/TB it can be concluded that the nutritional status of children at TKIT Ananda Jember is classified as not good.